Geophysical Survey on Open Dumping Landfill for Monitoring Spread of Leachate: A Case Study in Pekanbaru, Riau, Indonesia - Adi Suryadi; Frezy Ukhuah Islami; Husnul Kausarian; Dewandra Bagus Eka Putra (UIR PRESS, 2020)
Pekanbaru is a city in Indonesia with high population growth. The increasing amount of the population has a parallel relationship with the increasing quantity of waste disposal. This study has been conducted on an open dumping landfill at Pekanbaru that surrounded by residential areas. Waste disposal produces leachate as a threat to surface water and groundwater resources. This study aims to investigate the contamination spread formed by leachate using the geophysical method. Direct Current Resistivity (DCR) has been used to produce 2 D Resistivity subsurface Models. Data acquisition has been done using multi-electrodes (32 electrodes) with spacing 2 m between electrodes. 2D Resistivity model produced, a contaminant from leachate represented by low resistivity value 26.1 - 870 Ωm. The deepest penetration of leachate that detected is around 3 m from the surface. It has been understood that leachate from the landfill of the study area is not contaminated groundwater yet. It confirmed by groundwater analysis at residential around the landfill area. By knowing the spreading of leachate, preventive action can be made to maintain the quality of groundwater resources.